Assessment of Physico-Chemical Parameters of River Water of Subarnarekha Basin In and Around Jharkhand Area. (International Journal of Scientific Research and Management (IJSRM), 2017)
The present investigation is aimed at assessing the current physico-chemical characteristics along the Subarnarekha river in Jhadkhand and Odisha.Eight samples were collected along the stretches of Subarnarekha basin during the period (Water Year) June-2012 to May-2013 on the first working day of every month.Various physico-chemical parameters like pH, TDS, ,EC,DO,BOD,TotalHardness,Totalalkalinity,sodium,potassium,calcium,magnesium etc. were analysed. The study reveals that most of the parameters were found within permissible limits recommended by WHO and Indian Council of Medical Research (ICMR).